Drought and Heat Differentially Affect XTH Expression and XET Activity and Action in 3-Day-Old Seedlings of Durum Wheat Cultivars with Different Stress Susceptibility - Iurlaro, Andrea; De Caroli, Monica; Sabella, Erika; De Pascali, Mariarosaria; Rampino, Patrizia; De Bellis, Luigi; Perrotta, Carla; Dalessandro, Giuseppe; Piro, Gabriella; Fry, Stephen C.; Lenucci, Marcello S. (Frontiers in Plant Science, 2016)
Heat and drought stress have emerged as major constraints for durum wheat production. In the Mediterranean area, their negative effect on crop productivity is expected to be exacerbated by the occurring climate change. Xyloglucan endotransglucosylase/hydrolases (XTHs) are chief enzymes in cell wall remodeling, whose relevance in cell expansion and morphogenesis suggests a central role in stress responses. In this work the potential role of XTHs in abiotic stress tolerance was investigated in durum wheat. The separate effects of dehydration and heat exposure on XTH expression and its endotransglucosylase (XET) in vitro activity and in vivo action have been monitored, up to 24 h, in the apical and sub-apical root regions and shoots excised from 3-day-old seedlings of durum wheat cultivars differing in stress susceptibility/tolerance. Dehydration and heat stress differentially influence the XTH expression profiles and the activity and action of XET in the wheat seedlings, depending on the degree of susceptibility/tolerance of the cultivars, the organ, the topological region of the root and, within the root, on the gradient of cell differentiation. The root apical region was the zone mainly affected by both treatments in all assayed cultivars, while no change in XET activity was observed at shoot level, irrespective of susceptibility/tolerance, confirming the pivotal role of the root in stress perception, signaling, and response. Conflicting effects were observed depending on stress type: dehydration evoked an overall increase, at least in the apical region of the root, of XET activity and action, while a significant inhibition was caused by heat treatment in most cultivars. The data suggest that differential changes in XET action in defined portions of the root of young durum wheat seedlings may have a role as a response to drought and heat stress, thus contributing to seedling survival and crop establishment. A thorough understanding of the mechanisms underlying these variations could represent the theoretical basis for implementing breeding strategies to develop new highly productive hybrids adapted to future climate scenarios.